Directed phase formation of functional glass-crystalline coatings for ceramics in TiO₂-Al₂O₃-SiO₂ system - Lisachuk, G.V.; Bilostotska, L.O.; Trusova, Yu.D.; Vernygora, K.P.; Podchasova, K.V.; Krivobok, R.V. (Functional Materials, 2015)
Possibility of obtaining of thin crystallization (less than 4 μm) of non-fritt coatings by adding significant number (up to 15 wt.%) of tin dioxide (SnO2₂) to their compounds was studied. It was found that titaniferous coatings, containing SnO₂ as mineralizer, promotes the directed mullite and stable anosovite phase formation. Glass-crystalline coatings with the easy-to-clean and biostability properties were obtained upon moulding temperature up to 1200°C.